Consumer Protection Against Food That Contains Harmful Substances (Study of the Decision of the Judge of the District Court of Bale Bandung 831/Pid.Sus/2016/PN.Blb) - Rezi; Aryono; Friska Anggun (Universitas Duta Bangsa Surakarta, 2022)
ABSTRACT This study aims to determine consumer legal protection for food products marketed by business actors and to determine legal sanctions against business actors if consumers are harmed by consuming food containing hazardous substances. This research is based on normative juridical law research with secondary data collection, to prove consumer protection against foods containing hazardous substances based on consumer protection laws. The data obtained were analyzed qualitatively. Law No. 8 of 1999 provides limits for business actors and consumers, and provides specific and direct tasks regarding consumer protection, as stated in Article 45 of the Act mentioned above. The findings reveal that the Consumer Protection Law, apart from regulating the rights and obligations of consumers, also regulates the rights and obligations of business actors. Based on article 8 number (1) of Law no. 8 of 1999 concerning Consumer Protection, namely: Business actors are prohibited from producing and/or trading products and/or services that: 1) do not include the expiration date or period of best use/utilization of certain products. 2) deliberately does not include labels or make product descriptions containing product name, size, net or net weight/content, composition, rules of use, date of manufacture, side effects, name and address of business actor and other information for use which according to the provisions must be be included. The Consumer Protection Law, apart from regulating the rights and obligations of consumers, also regulates the rights and obligations of business actors. Keywods: Consumer Protection, Hazardous Materials, Food Products